Double Frost Suture Technique for Simultaneous Skin Grafting of the Upper and Lower Eyelids. Issue 6 (November 2021) - DeMaria, Lauren N.; Tran, Ann Q.; Tooley, Andrea A.; North, Victoria S.; Flores, Roberto L.; Lisman, Richard D.; Belinsky, Irina
Abstract : The double Frost suture is a useful supplement to the reconstruction of ipsilateral upper and lower eyelid defects with full-thickness skin grafts. This technique involves silk traction sutures that overlap the upper and lower eyelids to place them on maximal stretch after placement of 2 full-thickness skin grafts. It has the added benefit of protecting the cornea and compressing both grafts under 1 bolster. The authors illustrate this technique in 2 pediatric cases—a congenital melanocytic kissing eyelid nevus and a periocular burn. Each case resulted in large upper and lower anterior lamellar defects, which were reconstructed with supraclavicular and retroauricular free skin grafts. The double Frost sutures counter vertical cicatricial forces during graft healing, obviating the need for staged procedures. Both described cases resulted in excellent graft survival with minimal contracture. Abstract : The double Frost suture technique enhances reconstruction of large ipsilateral upper and lower eyelid defects by applying compression and overstretch to simultaneous full-thickness skin grafts in a one-stage procedure.